2010
DOI: 10.1002/elsc.200900111
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Cr(VI) from aqueous solution by fungal biomass

Abstract: Chromium compounds are released by industrial processes including leather production, mining, petroleum refining, in textile industry and dyeing. They are a significant threat to the environment and public health because of their toxicity. Removal of hexavalent chromium by living biomass of different fungi was effective in the order of Aspergillus terricola>Aspergillus niger>Acremonium strictum>Aureobasidium pullulans>Paecilomyces variotii>Aspergillus foetidus>Cladosporium resinae>Phaneroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The highest uptake of Pb (59.67 mg/g) by A. terreus indicated more binding sites on cell wall of this fungus and its potential as biosorbent to remove Pb from industrial wastewater containing higher concentration of Pb. Similar results with respect to differential Pb uptake by different fungi were reported by earlier workers [15][16][17][18][19][20].…”
Section: Growth and Uptake Of Pb By Fungal Isolatessupporting
confidence: 91%
“…The highest uptake of Pb (59.67 mg/g) by A. terreus indicated more binding sites on cell wall of this fungus and its potential as biosorbent to remove Pb from industrial wastewater containing higher concentration of Pb. Similar results with respect to differential Pb uptake by different fungi were reported by earlier workers [15][16][17][18][19][20].…”
Section: Growth and Uptake Of Pb By Fungal Isolatessupporting
confidence: 91%
“…The biosorption of metal ions by microbial biomass has several advantages over other conventional methods used to remove the heavy metals. It was reported that metabolism-independent metal binding to the cell walls and external surfaces is the only mechanism present in the case of non-living biomass (Ahluwalia and Goyal, 2003). Metabolism-independent uptake essentially involves ionic, chemical and physical adsorption process.…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Cr (VI) adsorption curves conformed to level 2 kinetics curve and were spontaneous, endothermic, and highly affinitive to the biomass. Ahluwalia [19] researched 8 living fungal biomass, found that they had different reduction abilities to hexavalent chromium, but for death, dry biomass, it showed a greater reduction activities. Phanerochaete chrysosporium could process chrome to the 0.1 mg/l of allowable scope in outflow, and the processing ability could not be influenced by other metal ions (Fe, Zn, Ni).…”
Section: Biological Degradationmentioning
confidence: 99%